Studi Komparasi Hasil Belajar Peserta Didik Melalui Model Pembelajaran Kontekstual dan Inovasi Guru di SD N 1 dan 3 Selang Kebumen - Siti Anisatun Nafi'ah; Maemonah . (LITERASI (Jurnal Ilmu Pendidikan), 2018)
This thesis aims to: (1) analyze the influence of contextual learning model on the learning outcomes of the third grade students of SDN 1 and 3 Selang, (2) analyze the influence of contextual learning model through teacher innovation on the learning outcomes of the third grade students of SDN 1 and 3 Selang (3) analyze the differences of contextual learning model and teacher innovation on the learning outcomes of the third grade students of SDN 1 and 3 Selang.This research was conducted in SDN 1 and 3 Selang using sequential explanatory research method. The first stage using qualitative method. Data collection techniques used were interviews, and observations. The second stage using quantitative. Data collection techniques used questionnaires, tests, observation sheets, performance tasks and projects. Data analysis techniques used were qualitative and quantitative.Based on the results, the learning outcomes of learners in the cognitive domain of contextual learning model don’t give a significant influence compared to the contextual learning model through teacher innovation. The result of significance in the first is 0.302 > 0.05, second is 0.244 > 0.05, third is 0.081 > 0.05, fourth is 0.923 > 0.05, then Ho is accepted. The contextual learning model through teacher innovation gives a significant influence on the domain of attitude and psychomotor. The attitude is such as active, cooperative, and responsible. The psychomotor is such as observation, conclusion, money management, and saving skills. Keywords: Contextual Learning Model, Teacher Innovation, Learning Outcomes